2004
DOI: 10.1016/s0005-7967(03)00138-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of psychologists’ attitudes towards and utilization of exposure therapy for PTSD

Abstract: Although research supports the efficacy of exposure therapy for PTSD, some evidence suggests that exposure is under-utilized in general clinical practice. The purpose of this study was to assess licensed psychologists' use of imaginal exposure for PTSD and to investigate perceived barriers to its implementation. A total of 852 psychologists from 3 states were randomly selected and surveyed. An additional 50 members of a trauma special interest group of a national behavior therapy organization were also surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
564
9
24

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 666 publications
(634 citation statements)
references
References 14 publications
27
564
9
24
Order By: Relevance
“…We, however, found that the posttreatment PTSD symptom amelioration persisted up to six months. Second, TFT programmes may evoke serious adverse events or symptom exacerbations (Becker, Zayfert, & Anderson, 2004; van Minnen et al, 2010) and these risks are assumed to be higher in intensive treatment programmes and in more vulnerable PTSD patients with ICD-11 Complex PTSD symptoms such as the present population. We found no evidence for this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…We, however, found that the posttreatment PTSD symptom amelioration persisted up to six months. Second, TFT programmes may evoke serious adverse events or symptom exacerbations (Becker, Zayfert, & Anderson, 2004; van Minnen et al, 2010) and these risks are assumed to be higher in intensive treatment programmes and in more vulnerable PTSD patients with ICD-11 Complex PTSD symptoms such as the present population. We found no evidence for this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effectiveness of trauma-focused treatments (TFTs) for post-traumatic stress disorder (PTSD) (Watts et al, 2013), these treatments are underused in clinical practice, even among trained clinicians (Becker, Zayfert, & Anderson, 2004; Hipol & Deacon, 2013). For instance, in one study it was shown that prolonged exposure (PE) was hardly used by therapists in the USA (Becker et al, 2004), a finding that was replicated in Europe for both PE and eye movement desensitization and reprocessing (EMDR) (van Minnen, Hendriks, & Olff, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in one study it was shown that prolonged exposure (PE) was hardly used by therapists in the USA (Becker et al, 2004), a finding that was replicated in Europe for both PE and eye movement desensitization and reprocessing (EMDR) (van Minnen, Hendriks, & Olff, 2010). Many therapists feel uncomfortable in directly addressing traumatic memories and evoke high levels of fear in the treatment sessions (Becker et al, 2004; Grimmett & Galvin, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations